The Surgical Correction of Urogenital Sinus in Patients with DSD: 15 Years after Description of Total Urogenital Mobilization in Children - Ludwikowski, Barbara M.; González, Ricardo (Frontiers in Pediatrics, 2013)
Total urogenital sinus mobilization has been applied to the surgical correction o virilized females and has mostly replaced older techniques. Concerns have been raised about the effect of this operation on urinary continence. Here we review the literature on this topic since the description of the technique 15 years ago. Technical aspects and correct nomenclature are discussed. We emphasize that the term “total” refers to an en-bloc dissection and not to the extent of the proximal dissection. No cases of urinary incontinence have been reported following this operation. It is yet too early to evaluate results regarding sexual function but it is likely that the use of a posterior skin flap to augment the introitus will minimize the development of introital stenosis.